Promising therapeutic mechanism for Chinese herbal medicine in ameliorating renal fibrosis in diabetic nephropathy - Wang, Shengju; Qin, Shuai; Cai, Baochao; Zhan, Jihong; Chen, Qiu (Frontiers in Endocrinology, 2023)
Diabetic nephropathy (DN) is one of the most serious chronic microvascular abnormalities of diabetes mellitus and the major cause of uremia. Accumulating evidence has confirmed that fibrosis is a significant pathological feature that contributes to the development of chronic kidney disease in DN. However, the exact mechanism of renal fibrosis in DN is still unclear, which greatly hinders the treatment of DN. Chinese herbal medicine (CHM) has shown efficacy and safety in ameliorating inflammation and albuminuria in diabetic patients. In this review, we outline the underlying mechanisms of renal fibrosis in DN, including oxidative stress (OS) generation and OS-elicited ASK1-p38/JNK activation. Also, we briefly summarize the current status of CHM treating DN by improving renal fibrosis. The treatment of DN by inhibiting ASK1 activation to alleviate renal fibrosis in DN with CHM will promote the discovery of novel therapeutic targets for DN and provide a beneficial therapeutic method for DN.